2008
DOI: 10.1007/s11258-008-9460-8
|View full text |Cite
|
Sign up to set email alerts
|

Population structures and individual performances of Trillium grandiflorum in hedgerow and forest habitats

Abstract: In agricultural landscapes, linear habitats, such as hedgerows at field margins increase structural connectivity among forest patches, potentially providing dispersal corridors for forest herbs. The spatial structure of linear habitats, however, also results in edge effects and perturbations that can influence the individual and population performance of forest plants. This study compares the stage structure and components of growth and reproduction of 14 Trillium grandiflorum populations in hedgerows and fore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 74 publications
0
20
0
Order By: Relevance
“…Relatively few species have higher germination in darkness than in light (Baskin and Baskin, 1998). Studies on seeds with MPD that do not have double dormancy have found high percentages of germination in light (Hidayati et al, 2000a, 2000b, 2001; Baskin et al, 2002; Kondo et al, 2002, 2004, 2005, 2006; Walck and Hidayati, 2004b; Karlsson and Milberg, 2007; Kondo and Sato, 2007; Vandelook et al, 2007, 2009; Phartyal et al, 2009a, b; Vandelook and Assche, 2008, 2009). In seeds with double dormancy, studies on six plant species were conducted either in pots or (presumably) outdoors (Barton and Schroeder, 1942; Barton, 1944; Whigham, 1974), and we assume that seeds were in darkness while buried in soil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relatively few species have higher germination in darkness than in light (Baskin and Baskin, 1998). Studies on seeds with MPD that do not have double dormancy have found high percentages of germination in light (Hidayati et al, 2000a, 2000b, 2001; Baskin et al, 2002; Kondo et al, 2002, 2004, 2005, 2006; Walck and Hidayati, 2004b; Karlsson and Milberg, 2007; Kondo and Sato, 2007; Vandelook et al, 2007, 2009; Phartyal et al, 2009a, b; Vandelook and Assche, 2008, 2009). In seeds with double dormancy, studies on six plant species were conducted either in pots or (presumably) outdoors (Barton and Schroeder, 1942; Barton, 1944; Whigham, 1974), and we assume that seeds were in darkness while buried in soil.…”
Section: Discussionmentioning
confidence: 99%
“…Many aspects of the biology of T. camschatcense have been studied: phenology, seasonal growth pattern (Ohara and Kawano, 2005), genetic diversity, breeding system (Ohara et al, 1996, 2006; Ohara and Kawano, 2005; Kubota et al, 2008), resource allocation (Tomimatsu and Ohara, 2006b), and seed dispersal by myrmecochory (Ohara and Kawano, 2005). The seedling stage of T. camschatcense is highly affected by edge effects (Tomimatsu and Ohara 2004, 2006a) as is that of other Trillium species (Jules and Rathcke, 1999; Schmucki and de Blois, 2009). Tomimatsu and Ohara (2004) found that the density of T. camschatcense seedlings was considerably lower at the edge than in the interior of the forest, and they suggested that microclimatic conditions associated with the edge environment might be deleterious to seed germination.…”
mentioning
confidence: 99%
“…The ranking was based on the results of studies previously conducted in this area and on related research from other countries (see above). It is known, for example, that hedgerows on average provide plants with a higher relative irradiance, higher soil nitrogen and lower soil moisture compared to forests (Schmucki and de Blois 2009). Therefore high Ellenberg values for light and nitrogen and low values for soil moisture were transformed into low rank scores.…”
Section: Data Collectionmentioning
confidence: 99%
“…In 2009-2010, the effects of forest cover on vital rates were smaller, resulting in smaller contributions (Fig. The larger light availability in these sites could favor resource acquisition and accumulation by adults in these areas (Schmucki and De Blois 2009), enhancing their re-growth ability and long-term survival. The LTRE contributions also indicated that in both yearly intervals, the increase in l with forest edge Figure 3.…”
Section: Question 3: Components Of Landscape Structure and Vital Ratementioning
confidence: 99%
“…However, we also found an increased probability of survival of reproductive adults in edge-rich sites. The larger light availability in these sites could favor resource acquisition and accumulation by adults in these areas (Schmucki and De Blois 2009), enhancing their re-growth ability and long-term survival. Overall, the effects of increased edge length tended to have a positive effect on vital rates.…”
Section: Question 3: Components Of Landscape Structure and Vital Ratementioning
confidence: 99%